The Effectiveness of Distance Learning Using the Google Classroom Learning Management System During the Covid-19 Pandemic - Puji Hastutiningsih; Ade Ariyono (Teknodika, 2023)
The problem of the COVID-19 pandemic growth is highly influential in various aspects, including education. It is necessary to conduct learning using a distance learning model due to the development of COVID-19 numerical data and government policies prohibiting face-to-face learning in response to the COVID-19 pandemic. It forces teachers to conduct efficient instruction to boost student learning activities. This study thus aims to determine the effectiveness of distance learning using the Google Classroom Learning Management System (LMS), which includes planning, implementation, and evaluation and ends by making conclusions about the effective use of the Google Classroom Learning Management System. This study employed a qualitative approach with data collection techniques in the form of interviews, observation, and documentation studies. From the research results, it was found that 46% stated that they strongly agreed, 27% agreed, and 27% quite agreed that the application of Google Classroom influenced the teaching and learning process in distance learning. In addition, 58% admitted that they strongly agreed, 30% agreed, and 13% quite agreed that the design and production of learning materials on Google Classroom had been effective. Further, all teachers had uploaded the documents needed for learning evaluation, and students responded that Google Classroom could be a learning medium, helped in collecting assignments and quizzes, had easy-to-understand features, and they did not feel given many assignments because learning in Google Classroom became more effective and did not take a long time. Nonetheless, the results of interviews with students revealed that there were student obstacles in the distance learning implementation, i.e., the availability of internet quota and mobile phone specifications, which were slow in accessing Google Classroom, and some students did not have mobile phones, which was related to the financial ability of the student's parents. Hence, it can be concluded that using the Google Classroom Learning Management System has been effective in distance learning.